Implementation of wavelet-based robust differential control for electric vehicle application - Febin Daya, J.L.; Sanjeevikumar, Padmanaban; Blaabjerg, Frede; Wheeler, Patrick; Ojo Olorunfemi, Joseph (IEEE, 2015)
This research letter presents the modeling and simulation of electronic differential, employing a novel wavelet controller for two brushless dc motors. The proposed controller uses discrete wavelet transform to decompose the error between actual and reference speed. Error signal that is actually given by the electronic differential based on throttle and steering angle is decomposed into frequency components. Numerical simulation results are provided for both wavelet and proportional-integral-derivate controllers. In comparison, the proposed wavelet control technique provides greater stability and ensures smooth control of the two back driving wheels.